2003
DOI: 10.1094/phyto.2003.93.12.1553
|View full text |Cite
|
Sign up to set email alerts
|

Nontoxigenic Strains of Pseudomonas syringae pv. phaseolicola Are a Main Cause of Halo Blight of Beans in Spain and Escape Current Detection Methods

Abstract: From a collection of 152 pseudomonads isolated from diseased beans in Spain, 138 (91%) of the strains were identified as Pseudomonas syringae pv. phaseolicola and the rest as P. syringae pv. syringae. The P. syringae pv. phaseolicola strains produced typical water-soaked lesions on bean pods, although 95 of them did not produce phaseolotoxin in vitro. Ninety-four of these isolates did not produce the expected 0.5-kb product after polymerase chain reaction (PCR) amplification using primers specific for open rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
51
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 38 publications
1
51
0
Order By: Relevance
“…However, it was recently showed that more than 66% of the P. syringae pv. phaseolicola isolates causing field epidemics in Castilla y León, Spain, were nontoxigenic and did not contain DNA specific for the biosynthesis of phaseolotoxin (Rico et al, 2003;Oguiza et al, 2004). The strains of P. syringae pv.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…However, it was recently showed that more than 66% of the P. syringae pv. phaseolicola isolates causing field epidemics in Castilla y León, Spain, were nontoxigenic and did not contain DNA specific for the biosynthesis of phaseolotoxin (Rico et al, 2003;Oguiza et al, 2004). The strains of P. syringae pv.…”
mentioning
confidence: 99%
“…Incidentally, all the P. syringae pv. phaseolicola tox-strains analyzed so far also lacked other genes of the phaseolotoxin biosynthesis cluster and failed to produce phaseolotoxin (Rico et al, 2003;Oguiza et al, 2004). Additionally, the tox-isolates also failed to react with one of the few commercial antibodies for the serological detection of P. syringae pv.…”
mentioning
confidence: 99%
See 3 more Smart Citations